Linalool Impress Colorectal Cancer Deterioration by Mediating AKT/mTOR and JAK2/STAT3 Signaling Pathways. (11th July 2022) - Hou, Min; Zhang, Yakun; Huang, Qingmei; Zhan, Hongmei; Jia, Tingting; Li, Min; Hu, Jing; Zhao, Yanli
Abstract : Colorectal cancer (CRC) is one of the more common causes of cancer death worldwide. Chemotherapy is effective in the treatment of CRC, but it can produce a range of adverse effects that can significantly reduce the quality of life of CRC patients. The selection of drugs that are effective in treating CRC with few adverse effects is now an important task and is aimed at prolonging the survival of patients and improving their prognosis. In this study, CRC cells were treated with linalool using CRC cell lines as the study subjects, and cell viability, apoptosis, and cell migration were observed after treatment. Previous studies have demonstrated the therapeutic effects of linalool on CRC and its ability to inhibit CRC progression by modulating the AKT/mTOR and JAK2/STAT3 pathways.